2011
DOI: 10.1038/cdd.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse granzyme K has pro-inflammatory potential

Abstract: Granzymes (gzms) are key components of T-killer (Tc) cells believed to mediate pro-apoptotic activities. Recent evidence suggests that gzms also possess non-cytotoxic activities that contribute to host defense. In this study, we show that Tc cells from lymphocytic choriomeningitis virus (LCMV)-infected wild-type (wt) and gzm A/B-deficient mice express similar levels of gzmK protein, with both mouse strains efficiently controlling infection. GzmK, in recombinant form or secreted by ex vivoderived LCMV-immune gz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
131
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 45 publications
11
131
1
Order By: Relevance
“…In addition, it has been shown recently that cord blood contains a small proportion of Th1, Th2, and Th17 effector memory-like CD4 + αβ T cells, indicating the functional plasticity of this subset (74). We also showed that fetal blood Vγ9Vδ2 T cells express a particular pattern of granzymes with high coexpression of granzymes A and K but no expression of the classical killer granzyme B (75,76). Perforin was enriched in Vγ9Vδ2 T cells at the RNA level but not at the protein level, in contrast to adult Vγ9Vδ2 T cells, which are known to express perforin, granzyme B, and granulysin protein (3).…”
Section: Discussionmentioning
confidence: 59%
“…In addition, it has been shown recently that cord blood contains a small proportion of Th1, Th2, and Th17 effector memory-like CD4 + αβ T cells, indicating the functional plasticity of this subset (74). We also showed that fetal blood Vγ9Vδ2 T cells express a particular pattern of granzymes with high coexpression of granzymes A and K but no expression of the classical killer granzyme B (75,76). Perforin was enriched in Vγ9Vδ2 T cells at the RNA level but not at the protein level, in contrast to adult Vγ9Vδ2 T cells, which are known to express perforin, granzyme B, and granulysin protein (3).…”
Section: Discussionmentioning
confidence: 59%
“…[8][9][10]24 Here, we have demonstrated that cell death can be induced when mGzmA is delivered by NKs via authentic CL/target cell interactions.…”
Section: Discussionmentioning
confidence: 79%
“…5,6 This oxidative stress is predicted to cause translocation of the SET complex into the nucleus, where GzmA cleaves components of the SET complex and induces DNA damage through single-stranded nicking, resulting in cell death. 5,7 However, these findings have been difficult to corroborate and recent studies from several independent groups using recombinant or native protease have reported that GzmA has little cytotoxicity [8][9][10] or that GzmA may simply enhance Pfp-mediated membranolysis. 8 In contrast, studies using GzmB À / À CTL suggest that GzmA does have a role in target cell death.…”
mentioning
confidence: 99%
“…Human gzmB has been shown to induce cell death in Jurkat cells by degradation of Mcl-1 and subsequent release of proapoptotic Bim (22,26,31). We therefore asked whether Bim also contributes to gzmB-mediated apoptosis in mice by incubating ex vivo mouse gzmB ϩ Tc cells with either WT or Bimdeficient 3T9 MEF cells (3T9 MEF.Bim Ϫ/Ϫ ).…”
Section: Resultsmentioning
confidence: 99%